(3GdCRgjI aj Yde GdMQhas - (3GdgQhj , Ydj Hf eMeO GdgQhj GdfMhj, CHh GdMSf,J (B370 (3g` s
(3ChdgG (B:s
(3SCdJfj CjOc Gddg Cf CLeY dc CHhGHkG ef GdfMh bO PcQfGgG eJaQbI aj cJGHfG GdedbH HGdPNGFQ, djSgd Ydjc MaXgG hbQGAJgG s
(3BNQgG (B:s
(3hbGd BNQ ef GddGA de jMLLf jHZjf pMSHI hdcf djbJdf GdHQF GdeZadG GdMeO ddg Ydi GdJeGe s
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS Hbde eJCNQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B686s
Keywords: (3GdfMhs